(untitled) (Research, Society and Development, 2022)
Sickle Cell Anemia (SCA) is a hematological, genetic, and chronic disease that often requires hospitalizations and constant outpatient care. This study aims to describe the steps in the elaboration of a book with the purpose of encouraging conversations with children with AF about the disease, explaining its functioning, symptomatology, and limitations it entails in daily life. The following steps were followed: a) preparation of the project, b) selection of content, through a literature review on symptoms and limitations arising from SCA; c) development of the story: choice of the school as the setting and of the character Amanda, a black girl, as the protagonist of the book; d) development of the pilot book; e) review and validation by experts: the material was analyzed by psychologists and doctors with experience in the subject and children without clinical diagnosis; f) adequacy of language and contents: the suggested adaptations were made; g) new submission of the material to the experts; h) finalization of the book: the material was illustrated, cataloged and printed. The main topics addressed in the story were: the need for eventual school absences, school physical activity restrictions, definitions of the disease, crisis, symptoms, and treatment. The storyline ends with the possibility of inserting the patient with SCA in an adapted routine at school and with tips for parents and teachers. The material produced can be used in various contexts, such as health care and school. Besides the educational character, the book can be used as an intermediary material facilitator for the affective expression of children with SCA who identify themselves with the experience of the character Amanda. (Support: Programa Unificado de Bolsas da Universidade de São Paulo - PUB-USP).